HISTÓRIA, MEMÓRIA E POLÍTICA EM PESSACH: A TRAVESSIA, DE CARLOS HEITOR CONY - Cella, Thiana Nunes (2016)
This dissertation makes an analysis of novel Pessach: a travessia, by the writer and journalist Carlos Heitor Cony, first published in 1967, in order to show how this novel dialogs with the contemporary historical moment of its publication; how it consolidated its position as a political realist novel, characterized by an effect of reaction to the repression and censorship current in the first years that the country lived under the military yoke; how it fits in the tradition of literary engagement with character of complaint and resistance, with political and ideological implications to the concrete reality of that time. The research methodology involves critical-analytical study, based on literature review and literary analysis of the novel, built on four points considered fundamental in the novel: the dialogue with the History, its memorialistic aspects, the questioning of individual and national identity and the political ideological engagement. Whereas the literature produced after the Military Coup, particularly that associated to memorialism is a fertile ground for revisiting and rethinking on various national issues of historical, ideological and political nature, the relevance of this work lies in to emphasize how Pessach: a travessia, allows to review and reflect on the disturbing events experienced in post 1964 years, a fact that becomes more accurate and impartial due to the temporal distance from the novel`s publication.